How does EGFR overexpression affect the development and treatment of rectal cancer? - Kozłowska-Geller, Monika A.; Lewitowicz, Piotr; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2018)
Epidermal growth factor (EGF) stimulates the proliferation of many different types of cells and plays an important role in the formation and growth of tumours. The interaction of EGF with cells is possible by the EGF receptor (EGFR) anchored in the cell membrane. Excess EGFR expression is found in approximately 25–82% of colorectal cancer cases. Attachment of EGF to EGFR results in a conformational change in the receptor, an increase in affinity for neighbouring receptors, receptor dimerisation, and activation of tyrosine kinase in the intraplasmic domain. Activation of EGFR leads to the initiation of the signal transduction pathway to the cell nucleus, via a number of proteins with enzymatic activity – secondary messengers, including KRAS and BRAF proteins. The assessment of the presence of mutations in the KRAS gene has become a standard element in the qualification of patients with advanced colorectal cancer for therapy with the use of monoclonal antibodies.